A Quantitative Study of Lettered Words in the Field of Computer Science. - LIU Jin ting; YU Qianfan; DU Zhenlei; WANG Qi (China Terminology, 2025)
This study employs quantitative analysis methods to examine the lettered words included in three editions of The Chinese Terms in Computer Science and Technology, conducting a detailed analysis of their distribution across different editions. Additionally, we investigate the morphemes of lettered words and their prevalence in specific subfields. The findings reveal a significant upward trend in both the quantity and proportion of lettered words, with their primary occurrence in emerging fields such as programming languages, networks, and communications. This research provides data support for the standardization of lettered words in computer science and offers a new perspective for their study.